2022
DOI: 10.3390/ijerph19052716
|View full text |Cite
|
Sign up to set email alerts
|

How News Agencies’ Twitter Posts on COVID-19 Vaccines Attract Audiences’ Twitter Engagement: A Content Analysis

Abstract: As the most important global news distributors, the big three international news agencies’ reports about COVID-19 vaccines have a great influence on people’s understanding of them. Based on the health belief model (HBM), we examined which constructs in the HBM were related to audiences’ Twitter engagement and the differences among the agencies. We content-analyzed 1162 COVID-19 vaccine-related tweets from three international news agencies’ Twitter accounts (@AFPespanol, @AP, @Reuters) from 2 December 2020 to 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 45 publications
2
11
0
Order By: Relevance
“…Sentiment analysis, as a machine learning technique, is used to detect the positive, negative, or neutral sentiments expressed in a text [ 22 ]. It is typically used to analyze the content of web-based texts [ 11 , 16 , 17 ], and has been increasingly popular in the field of public health and preventive medicine [ 23 , 24 , 25 , 26 , 27 ]. Thus far, there are several sentiment dictionaries such as the English NRC sentiment dictionary and Chinese Emotional Vocabulary Ontology Database of the Dalian University of Technology that have been widely used to uncover sentiments expressed in web texts [ 28 , 29 , 30 , 31 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sentiment analysis, as a machine learning technique, is used to detect the positive, negative, or neutral sentiments expressed in a text [ 22 ]. It is typically used to analyze the content of web-based texts [ 11 , 16 , 17 ], and has been increasingly popular in the field of public health and preventive medicine [ 23 , 24 , 25 , 26 , 27 ]. Thus far, there are several sentiment dictionaries such as the English NRC sentiment dictionary and Chinese Emotional Vocabulary Ontology Database of the Dalian University of Technology that have been widely used to uncover sentiments expressed in web texts [ 28 , 29 , 30 , 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…Social media such as Twitter, Sina Weibo and Facebook/Meta are platforms for free expression [ 10 , 11 , 12 ] and can provide extensive and valuable information to explore users’ awareness and sentiments on major public health events such as COVID-19 vaccinations [ 13 , 14 ]. Moreover, the analysis of social media data has become one of the most important fields of focus in medical informatics research.…”
Section: Introductionmentioning
confidence: 99%
“…Though most of the above studies examined whether the HBM constructs were presented in social media content, only a few studies examined the effect of the presence of these HBM constructs on citizen engagement ( Guidry et al, 2020 ; Wang and Lu, 2022 ). These limited studies suggest a critical application challenge: while the HBM has been tested extensively in the health behavior literature, its effectiveness may vary in different practical scenarios when it is applied in social media persuasion contexts.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These limited studies suggest a critical application challenge: while the HBM has been tested extensively in the health behavior literature, its effectiveness may vary in different practical scenarios when it is applied in social media persuasion contexts. For example, Wang and Lu (2022) found that the impacts of HBM constructs on citizens’ Twitter engagement were not stable and varied among the three big news agencies. Vaccination promotion using HBM constructs was effective for Reuters but seemed to be counterproductive for AFP.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation